The face of America : plays for young people - Brosius, Peter; Adams, Elissa (University of Minnesota Press, 2011)
The world of young people in the United States today is exhilaratingly global, enriched by the influences of many various cultures. With that, however, comes the need for children to retain confidence in their own heritage while empathizing with people who might seem very different from them. The protagonists of these four plays--written for the world-renowned Children's Theatre Company of Minneapolis--strive to achieve that balance with determination, love, and humor.